N-Methylphthalimide-substituted benzimidazolium salts and PEPPSI Pd–NHC complexes: synthesis, characterization and catalytic activity in carbon–carbon bond-forming reactions - Akkoç, Senem; Gök, Yetkin; İlhan, İlhan Özer; Kayser, Veysel (Beilstein Journal of Organic Chemistry, 2016)
A series of novel benzimidazolium salts (1–4) and their pyridine enhanced precatalyst preparation stabilization and initiation (PEPPSI) themed palladium N-heterocyclic carbene complexes [PdCl2(NHC)(Py)] (5–8), where NHC = 1-(N-methylphthalimide)-3-alkylbenzimidazolin-2-ylidene and Py = 3-chloropyridine, were synthesized and characterized by means of 1H and 13C{1H} NMR, UV–vis (for 5–8), ESI-FTICR-MS (for 2, 4, 6–8) and FTIR spectroscopic methods and elemental analysis. The synthesized compounds were tested in Suzuki–Miyaura cross-coupling (for 1–8) and arylation (for 5–8) reactions. As catalysts, they demonstrated a highly efficient route for the formation of asymmetric biaryl compounds even though they were used in very low loading. For example, all compounds displayed good catalytic activity for the C–C bond formation of 4-tert-butylphenylboronic acid with 4-chlorotoluene.
Keywords: arylation; benzimidazolium salts; catalysis; N-heterocyclic carbene; PEPPSI complex; Suzuki–Miyaura cross-coupling reaction

(untitled) - Wanzlick, H.-W.; Schönherr, H.-J. (Angew. Chem., Int. Ed. Engl., 1968)

(untitled) - Öfele, K. (J. Organomet. Chem., 1968)

(untitled) - Mangalum, A.; McMillen, C. D.; Tennyson, A. G. (Inorg. Chim. Acta, 2015)

(untitled) - Akkoç, S.; Gök, Y.; Akkurt, M.; Tahir, M. N. (Inorg. Chim. Acta, 2014)

(untitled) - Akkoç, S.; Gök, Y. (Appl. Organomet. Chem., 2014)

(untitled) - Serrano, J. L.; Pérez, J.; García, L.; Sánchez, G.; García, J.; Lozano, P.; Zende, V.; Kapdi, A. (Organometallics, 2015)

(untitled) - Lee, J.-Y.; Ghosh, D.; Lee, J.-Y.; Wu, S.-S.; Hu, C.-H.; Liu, S.-D.; Lee, H. M. (Organometallics, 2014)

(untitled) - Hashmi, A. S. K.; Lothschütz, C.; Böhling, C.; Hengst, T.; Hubbert, C.; Rominger, F. (Adv. Synth. Catal., 2010)

(untitled) - Li, Y.; Tan, C.-P.; Zhang, W.; He, L.; Ji, L.-N.; Mao, Z.-W. (Biomaterials, 2015)

(untitled) - Haque, R. A.; Choo, S. Y.; Budagumpi, S.; Iqbal, M. A.; Al-Ashraf, A. A. (Eur. J. Med. Chem., 2015)

(untitled) - Gök, Y.; Akkoç, S.; Albayrak, S.; Akkurt, M.; Tahir, M. N. (Appl. Organomet. Chem., 2014)

(untitled) - Boehme, C.; Frenking, G. (J. Am. Chem. Soc., 1996)

(untitled) - Viciu, M. S.; Navarro, O.; Germaneau, R. F.; Kelly, R. A.; Sommer, W.; Marion, N.; Stevens, E. D.; Cavallo, L.; Nolan, S. P. (Organometallics, 2004)

(untitled) - Zhang, T.; Shi, M.; Zhao, M. (Tetrahedron, 2008)

(untitled) - Polshettiwar, V.; Varma, R. S. (Tetrahedron, 2008)

(untitled) - Górna, M.; Szulmanowicz, M. S.; Gniewek, A.; Tylus, W.; Trzeciak, A. M. (J. Organomet. Chem., 2015)

(untitled) - Demir, S.; Özdemir, İ.; Çetinkaya, B.; Arslan, H.; VanDerveer, D. (Polyhedron, 2011)

(untitled) - Kantchev, E. A. B.; Ying, J. Y. (Organometallics, 2009)

(untitled) - Zhou, X.-X.; Shao, L.-X. (Synthesis, 2011)

(untitled) - Lin, Y.-C.; Hsueh, H.-H.; Kanne, S.; Chang, L.-K.; Liu, F.-C.; Lin, I. J. B.; Lee, G.-H.; Peng, S.-M. (Organometallics, 2013)

(untitled) - O'Brien, C. J.; Kantchev, E. A. B.; Valente, C.; Hadei, N.; Chass, G. A.; Lough, A.; Hopkinson, A. C.; Organ, M. G. (Chem. – Eur. J., 2006)

(untitled) - Yang, L.; Zhao, J.; Li, Y.; Ge, K.; Zhuang, Y.; Cao, C.; Shi, Y. (Inorg. Chem. Commun., 2012)

(untitled) - Zhao, J.; Yang, L.; Ge, K.; Chen, Q.; Zhuang, Y.; Cao, C.; Shi, Y. (Inorg. Chem. Commun., 2012)

(untitled) - Yaşar, S.; Şahin, Ç.; Arslan, M.; Özdemir, İ. (J. Organomet. Chem., 2015)

(untitled) - Rajabi, F.; Thiel, W. R. (Adv. Synth. Catal., 2014)

(untitled) - John, A.; Modak, S.; Madasu, M.; Katari, M.; Ghosh, P. (Polyhedron, 2013)

(untitled) - Akkoç, S.; Gök, Y. (Inorg. Chim. Acta, 2015)

(untitled) - Viciu, M. S.; Germaneau, R. F.; Nolan, S. P. (Org. Lett., 2002)

(untitled) - Kinzel, T.; Zhang, Y.; Buchwald, S. L. (J. Am. Chem. Soc., 2010)

(untitled) - Akkoc, S.; Gok, Y. (J. Coord. Chem., 2013)

(untitled) - Sun, J.; Fu, Y.; He, G.; Sun, X.; Wang, X. (Appl. Catal., B, 2015)

(untitled) - Liu, D.-X.; Gong, W.-J.; Li, H.-X.; Gao, J.; Li, F.-L.; Lang, J.-P. (Tetrahedron, 2014)

(untitled) - Ratniyom, J.; Chaiprasert, T.; Pramjit, S.; Yotphan, S.; Sangtrirutnugul, P.; Srisuratsiri, P.; Kongsaeree, P.; Kiatisevi, S. (J. Organomet. Chem., 2014)

(untitled) - Zhong, L.; Chokkalingam, A.; Cha, W. S.; Lakhi, K. S.; Su, X.; Lawrence, G.; Vinu, A. (Catal. Today, 2015)

(untitled) - Melvin, P. R.; Nova, A.; Balcells, D.; Dai, W.; Hazari, N.; Hruszkewycz, D. P.; Shah, H. P.; Tudge, M. T. (ACS Catal., 2015)